Social Action Project to Enhance Entrepreneurial Competencies - Widiastuti, Anik; Wulandari, Taat (Jurnal Pendidikan Indonesia, 2024)
Socio-creative entrepreneurship competencies are essential for learners to have as life skills. Socio-creative entrepreneurship competence can be promoted through projects. This study aims to analyze the effectiveness of social action projects in improving learners' social-creative entrepreneurship competencies. This research is a quasi-experimental posttest-pretest non-equivalent control group design involving 57 learners in a junior high school. Data on socio-creative entrepreneurship competencies were divided into three aspects: cognitive, affective, and psychomotor. Data on cognitive aspects were collected using test techniques and instruments in the form of essay test sheets. In contrast, affective and psychomotor aspects were collected using survey techniques and instruments in the form of questionnaire sheets. The results were analyzed using inferential descriptive statistics and the Mann-Whitney U test. The pre-test, post-test, and N-gain scores were compared. The statistical analysis results showed that social action projects affect socio-creative entrepreneurship competencies. The scores achieved by students in the class that used the social action project model were higher. Therefore, the social action project model is declared "effective" and can be applied in learning to improve social-creative entrepreneurship competencies. The learners' socio-creative entrepreneurship competence increased with the challenging atmosphere of social action projects in social studies learning. It is recommended that teachers use the social action project model to improve learners' entrepreneurial competencies as a preparation for the 21st century. Teachers should carefully adjust the social action project to the topic of the material to make it more contextual to life.